Transcription of cloned tRNA and 5S RNA genes in a Drosophila cell free extract. - Dingermann, T; Sharp, S; Appel, B; DeFranco, D; Mount, S; Heiermann, R; Pongs, O; Söll, D (Nucleic Acids Res, 1981)
We describe the preparation of a cell-free extract from Drosophila Kc cells which allows transcription of a variety of cloned eukaryotic RNA polymerase III genes. The extract has low RNA-processing nuclease activity and thus the major products obtained are primary transcripts.
Keywords: Animals; Cell-Free System; Cloning, Molecular; Drosophila; In Vitro Techniques; RNA; RNA Polymerase III; RNA, Transfer; Transcription, Genetic; Xenopus laevis